Digital equity for marginalised and displaced peoples. Issue 1 (18th October 2019) - Gilliland, Anne; McKemmish, Sue; Rolan, Gregory; Reed, Barbara
ABSTRACT: Upholding human rights – in particular for marginalised and displaced peoples – depends on exercising rights in data, information and records. In considering these information rights we face the challenge of designing ethical, adaptive, and inclusive information systems and technologies that support the actualisation of human rights, social justice, and Indigenous and First Nations sovereignty. Too often systems designed for an uncritical and generalised "happy centre" fail those on the margins, in all of their individualised complexity.The purpose of this panel will be to introduce an international initiative aimed at addressing this challenge, and to explore a developing research agenda for tackling the broad range of socio‐technical issues that comprise this wicked problem. It is hoped that this panel will galvanise the community towards action and engagement with this programme or its goals.